Introduction Of My Accounting Application to Smes Athif Laundry and Cahaya Laundry in Denokan Village - Anjar Lestari, Miftah Yusti; Nugraeni, Nugraeni (Institut Manajemen Wiyata Indonesia, 2024)
This community service initiative concentrated on aiding Small and Medium Enterprises (SMEs) in the laundry sector, specifically Athif Laundry and Cahaya Laundry in Denokan Village, Maguwoharjo. The primary goal was to improve human resources development and technological literacy within the local community. The laundry business, crucial for customer service, faced challenges in financial management and technological adaptation. The research emphasized the significance of profit generation for business sustainability, stressing the need for accurate financial records. Introducing the Akuntansi ku application, a digital accounting tool designed to automate transaction recording, the research aimed to empower SMEs in tracking income, expenses, debts, and receivables. The participatory methodology involved a survey, activity implementation, and results analysis. Athif Laundry and Cahaya Laundry were identified as suitable candidates for intervention, lacking financial statement preparation. The activities focused on educating and assisting SMEs in using the Akuntansi ku application, resulting in improved financial record-keeping efficiency, heightened motivation to maintain records, and enhanced organizational structure. In conclusion, the community service successfully equipped both laundries with knowledge and tools for effective financial record management through the Akuntansi ku application, emphasizing the importance of financial statements for evaluation and decision-making. The recommendation is to extend similar programs to other SMEs, promoting technological adoption for sustainable business growth.